Next generation immunotherapy for tree pollen allergies - Yan Su; Eliezer Romeu-Bonilla; Teri Heiland (Human Vaccines & Immunotherapeutics, 2017)
Tree pollen induced allergies are one of the major medical and public health burdens in the industrialized world. Allergen-Specific Immunotherapy (AIT) through subcutaneous injection or sublingual delivery is the only approved therapy with curative potential to pollen induced allergies. AIT often is associated with severe side effects and requires long-term treatment. Safer, more effective and convenient allergen specific immunotherapies remain an unmet need. In this review article, we discuss the current progress in applying protein and peptide-based approaches and DNA vaccines to the clinical challenges posed by tree pollen allergies through the lens of preclinical animal models and clinical trials, with an emphasis on the birch and Japanese red cedar pollen induced allergies.